Catalytic pyrolysis of high-density polyethylene over nickel-waste chicken eggshell/HZSM-5 - Mohamad Dzol, M. A.A.; Balasundram, Vekes; Shameli, Kamyar; Norazana, Ibrahim; Zainuddin, Abdul Manan; Ruzinah, Isha (Elsevier Ltd, 2022)
The main objective of the current work is to investigate the effect of nickel–waste chicken eggshell modified Hydrogen exchanged Zeolite Socony Mobil-5 (Ni-WCE/HZSM-5) on pyrolysis of high-density polyethylene (HDPE). Ni-WCE/HZSM-5 was synthesized via the impregnation incipient wetness (IWI) method with Ni and WCE mass loading of 4 and 12 wt% respectively. HZSM-5, CaO, WCE, WCE/HZSM-5, and Ni/HZSM-5 were prepared for comparison purposes with Ni-WCE/HZSM-5. All the synthesized catalysts were characterized for phase analysis, metal loading, surface morphology, and textural properties. The impregnation of nickel and WCE had significantly affected the original framework of HZSM-5, where the crystallinity percentage and average crystal size of HZSM-5 dropped to 44.97% and increased to 47.90 nm respectively. The surface morphology of HZSM-5 has drastically changed from a cubic-like shape into a spider web-like surface after the impregnation of WCE. The BET surface area of HZSM-5 has been lowered due to the impregnation of nickel and WCE, but the total pore volume has increased greatly from 0.2291 cm3/g to 0.2621 cm3/g. The catalyst performance was investigated in the pyrolysis of HDPE via a fixed bed reactor and the pyrolysis oil was further analysed to evaluate the distribution of C6 to C9> hydrocarbons. Among the tested catalytic samples, the highest pyrolysis oil yield was achieved by WCE (80%) followed by CaO (78%), WCE/HZSM-5 (63%), HZSM-5 (61%), Ni/HZSM-5 (44%) and Ni-WCE/HZSM-5 (50%). For hydrocarbon distribution in pyrolysis oil, the Ni/HZSM-5 produced the highest of total C6 and C7 hydrocarbons at 12% and 27% respectively followed by WCE/HZSM-5 (4% and 20%), non-catalytic (5% and 13%), Ni-WCE/HZSM-5 (0% and 15%), WCE (0% and 10%), HZSM-5 (0% and 6%) and CaO (0% and 0%).